2019
DOI: 10.2478/picbe-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Crowdfunding in Poland and Romania

Abstract: Given the difficulty to access traditional bank funding by creative businesses and start-ups, crowdfunding as an alternative way to finance innovative and creative projects has been adopted, enacted and successfully used by several Western countries, which can serve as best practice examples. However, in many countries crowdfunding is still an emerging phenomenon due to its novelty and variety, the general awareness regarding this alternative funding method being relatively low. The aim of this paper is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…donation-based crowdfunding has also been described as the acceptance of donations in terms of monetary resources through the internet without the expectation of receiving any form of reward (Noelia et al, 2021). According to Fanea-Ivanovici and Siemionek-Ruskań (2019), crowdfunding has developed from its initial forms such as donation-based and reward-based to more developed forms such as equity-based, lending-based, hybrid, and invoice trading crowdfunding. Crowdfunding if well utilized is useful in economic growth and development through exploiting the available opportunities in the community and innovation particularly in areas where obtaining finance is difficult (Hervé and Schwienbacher, 2018).…”
Section: Forms Of Crowdfundingmentioning
confidence: 99%
See 2 more Smart Citations
“…donation-based crowdfunding has also been described as the acceptance of donations in terms of monetary resources through the internet without the expectation of receiving any form of reward (Noelia et al, 2021). According to Fanea-Ivanovici and Siemionek-Ruskań (2019), crowdfunding has developed from its initial forms such as donation-based and reward-based to more developed forms such as equity-based, lending-based, hybrid, and invoice trading crowdfunding. Crowdfunding if well utilized is useful in economic growth and development through exploiting the available opportunities in the community and innovation particularly in areas where obtaining finance is difficult (Hervé and Schwienbacher, 2018).…”
Section: Forms Of Crowdfundingmentioning
confidence: 99%
“…There are connections between regular updates and successful projects. Yin et al (2019), study revealed that project updates and communication positively affect the success of crowdfunded campaigns. Additionally, Borst et al (2018), found a positive effect of project updates and tweets on the success of crowdfunding campaigns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The crowdfunding mechanisms spreads to more and more countries around the world. Yang et al, 2016;Dikaputra et al, 2019;Fanea-Ivanovici and Siemionek-Ruskan, 2019;Mendes-Da-Silva et al, 2019;Wang and Xue, 2019 Crowdfunding enables the democratizing of financing by eliminating barriers and diminishing restrictions. It supports the equitable distribution of financing for innovation and the underestimated economic power of investor-users.…”
Section: Choy and Schlagwein 2016mentioning
confidence: 99%
“…Crowdfunding mechanisms are legally recognized by the governments of more and more countries, which leads to their rapid development and increase in popularity worldwide, beyond the traditional western space. The development is rapid or promising in countries such as China (Wang and Xue, 2019 ) or ASEAN-5 (Indonesia, Malaysia, Singapore, Philippines, and Thailand) (Dikaputra et al, 2019 ), Eastern-European countries such as Poland and Romania (Fanea-Ivanovici and Siemionek-Ruskan, 2019 ), but still hesitant in African countries (Jaziri and Miralam, 2019 ).…”
Section: Introductionmentioning
confidence: 99%